Specification for design and manufacture of water-tube steam generating plant ( including superheraters, reheaters and steel tube economizers ) - British Standards Institution (London BSI, 1992)
Materials and design stresses, workmanship, inspection, testing, documentation and marking, valves, gauges and fittings of a steam generating plant subject to internal pressure and parts of steam and water heating plant
Replaced By BS 1113:1998
Revised, Withdrawn
Cross References BS 10, BS 21, BS 499:Part 1, BS 639, BS 709, BS 759:Part 1, BS 806, BS 1134, BS 1501:Part 1, BS 1501:Part 2, BS 1501:Part 3, BS 1502, BS 1503, BS 1504, BS 1515, BS 1560:Section 3.1, BS 1640:Part 1, BS 1821, BS 1957, BS 1965:Part 1, BS 2486, BS 2600:Part 1, BS 2600:Part 2, BS 2633, BS 2910, BS 3059:Part 1, BS 3059:Part 2, BS 3500, BS 3601, BS 3602:Part 1, BS 3602:Part 2, BS 3604:Part 1, BS 3605:Part 1, BS 3640, BS 3688:Part 1, BS 3799, BS 3889:Part 1, BS 3889:Part 2A, BS 3915, BS 3920, BS 3923:Part 1, BS 3923:Part 2, BS 3971, BS 4080, BS 4124, BS 4204, BS 4504:Section 3.1, BS 4570, BS 4677, BS 4870:Part 1, BS 4871:Part 1, BS 4882, BS 5044, BS 5046, BS 5135, BS 5447, BS 5500, BS 5750, BS 5762, BS 5970, BS 5996, BS 6072, BS 6208, BS 6443, BS 6693:Part 2, BS 6759:Part 1, BS EN 10002-1, BS EN 10045-1, PD 6493, PD 6510, ASME Boiler and Pressure Vessel Code Section VIII Division 1, ASTM E 446, ASTM E 186, ASTM E 125-63, ANSI/ASME BPV-VIII-I, Factories Act 1961, Health and Safety Executive Standards significant to health and safety at work
Replaces BS 1113:1989
Keywords: Water-tube boilers -- Standards